2009
DOI: 10.1016/j.neuropsychologia.2009.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Increased intra-individual reaction time variability in attention-deficit/hyperactivity disorder across response inhibition tasks with different cognitive demands

Abstract: One of the most consistent findings in children with ADHD is increased moment-to-moment variability in reaction time (RT). The source of increased RT variability can be examined using ex-Gaussian analyses that divide variability into normal and exponential components and Fast Fourier transform (FFT) that allow for detailed examination of the frequency of responses in the exponential distribution. Prior studies of ADHD using these methods have produced variable results, potentially related to differences in tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
239
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(268 citation statements)
references
References 40 publications
(77 reference statements)
25
239
3
1
Order By: Relevance
“…Recent research by the same group (Di Martino et al, 2008) as well as others (e.g. Johnson et al, 2007;Vaurio et al, 2009) have also found a predictable pattern of increased power in VLF RTV (<0.1 Hz) in children with ADHD. In contrast, Geurts et al (2008) did not find any evidence for increased RTV in children with ADHD in terms of oscillatory power after applying spectral analysis, ex-Gaussian techniques and intra-individual variability analysis.…”
Section: Introductionmentioning
confidence: 66%
“…Recent research by the same group (Di Martino et al, 2008) as well as others (e.g. Johnson et al, 2007;Vaurio et al, 2009) have also found a predictable pattern of increased power in VLF RTV (<0.1 Hz) in children with ADHD. In contrast, Geurts et al (2008) did not find any evidence for increased RTV in children with ADHD in terms of oscillatory power after applying spectral analysis, ex-Gaussian techniques and intra-individual variability analysis.…”
Section: Introductionmentioning
confidence: 66%
“…Several studies in children and adolescents have applied exGaussian analyses to RT data and have shown consistently that increased τ is associated with ADHD. [6][7][8][9][10][11][12][13][14] To our knowledge, the present study is the first of this size performed in adults that used ex-Gaussian analyses to demonstrate that these childhood findings may represent a persistent deficit in patients with ADHD. In addition, the correlation of τ with inattention symptoms supports earlier literature suggesting that excessively long RTs represent lapses of attention.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] Compared with reports on τ, reports on alterations of μ and σ in patients with ADHD have been less consistent, and findings seem more taskdependent. 10 The disorder has been associated with decreased μ, 7,9,12 increased σ, 7,9,[12][13][14] or no differences in μ 8,11,13,14 or σ. 8,11 These studies show that ADHD-related RTV is predominantly determined by extremely long RTs, which are best captured by an elevation in τ.…”
Section: Introductionmentioning
confidence: 99%
“…Second, intraindividual variability in RTs has been linked to impairments of attention and executive function (e.g., attention-deficit hyperactivity disorder, ADHD), such that more erratic responding is related to greater deficits (SonugaBarke & Castellanos, 2007;Stuss, Murphy, Binns, & Alexander, 2003;West, Murphy, Armilio, Craik, & Stuss, 2002). For example, even when overall speed is controlled, those with ADHD show more variable correct responses and more prominent RT fluctuations every 12-40 s (Castellanos, Sonuga-Barke, Milham, & Tannock, 2006;Di Martino et al, 2008;Vaurio, Simmonds, & Mostofsky, 2009). Important to the goals of the present study, previous work has yet to explore changes in within-subjects response variability as attention fluctuates over time (for one exception, see Faulkner, 1962).…”
Section: Rt Fluctuations and Attentionmentioning
confidence: 99%